Pengaruh Kepemilikan Manajerial, Leverage, dan Profitabilitas Terhadap Tax Avoidance pada Perusahaan Manufaktur - Bornok Situmorang; Vivian Anastasia (LPPM Universitas Ibnu Sina, 2021)
This study aims to determine the effect of managerial ownership, leverage, and profitability on tax avoidance of the manufacturing companies listed on Indonesia Stock Exchange (IDX) from 2016-2019. The sample selection in this study uses a purposive sampling technique. This research is a quantitative research with secondary data. The data analysis technique uses multiple linear regression analysis with the help of SPSS (Statistical Product and Service Solution) software version 22. The results of the research partially show that managerial ownership has no significant effect on tax avoidance, leverage has no significant effect on tax avoidance, and profitability has significant effect on tax avoidance. Simultaneous research results indicate that managerial ownership, leverage, and profitability together have a significant effect on tax avoidance.